Non-Fatal strangulation/suffocation in context of gender violence: Medicolegal aspects and implications in clinical practice: Estrangulación/sofocación no fatal en el contexto de violencia de género: aspectos médico-legales e implicancias para la práctica clínica - Núñez Garrido, Mónica Andrea (2024)
Despite the numerous efforts of the international community to eradicate all forms of violence against women, this problem is far from being resolved. According to the UN, one in three women has suffered physical or sexual violence from an intimate partner, sexual violence outside the couple, or both at least once in their life. Addressing this problem as a social health need of population groups allows an approach to gender violence as a collective health problem. At the level of physical violence, strangulation/suffocation has been identified as one of the most lethal forms of domestic violence and sexual assault. Victims of domestic violence who have been choked or strangled are 7.5 times more likely to be killed by their partner. A victim of strangulation/suffocation can lose consciousness in seconds or die within minutes, days or weeks after the attack, as well as suffer permanent brain damage or disability or emotional trauma. Recently, legal changes have been generated in the configuration of this crime,  the penalties have increased in United Kingdom, the United States, Australia and New Zealand. The current non-systematic narrative review of literature sought to explore updated medico-legal aspects of non-fatal strangulation/suffocation in the context of gender violence, and are highlightedrelevant implications for clinical practice.